Learning behaviours and motivation to learn in various cultural backgrounds - Hashim, Junaidah; Wok, Saodah (2010)
Evidences showed that students came from different country brought difference style and learning behavior which leads to differing pedagogical preferences (Gilleard, 1998; Rodrigues, 2005; Rodrigues, et al.,2000). This study examines the influence of culture on learning behaviors and motivation to learn among international students. Comparison is made based on four Hofstede cultural dimensions. This study adopted the student learning behavior instrument developed by Leung and Fung (2005). Sample for respondents is targeted on international students who are currently studying in one of the international university in Malaysia. In total, 246 respondents from 13 countries participated in this study. The findings revealed that Hofstede cultural dimension holds true for power distance in an educational setting. Students from high power distance cultures are likely to exhibit respect to lecturer, students from high individualism cultures are likely to exhibit individualistic learning behavior. However, it is found that there is no difference between high and low masculinity cultural dimension. There is a strong correlation between learning behavior and motivation to learn among the students where motivation to learn variance is 51.8 per cent explained by the learning behaviors of the students. The implications of the study are discussed.